Deployment Strategies for Protected Long-Reach PON - Ruffini, Marco (My University, 2012)
The mass deployment of ?bre access networks is probably the most important network upgrade strategy for operators over the coming decade. Next generation networks, and in particular the Long-Reach Passive Optical Network (LR-PON) solution, aim to increase long term economic viability and sustainability of Fibre-To-The-Premises (FTTP) deployment. The LR-PON solution achieves this by minimising the number of nodes and the amount of electronic equipment required within the network. Since a LR-PON replaces the metro backhaul network, which is usually a protected part of the network, protecting the long reach part of LRPON network against failures becomes a critical issue that needs to be taken into account. In this paper we introduce a novel protection mechanism that, by spreading the load generated by a node failure over the network, can signi?cantly reduce the overall protection capacity required. We then present a practical FTTP deployment scenario based on our protected LR-PON architecture for a European country. The problem is modeled using Integer Linear Programming and the optimisation results, obtained using a real dataset provided by a national operator, show that a small number of Metro/Core nodes can provide protected connection to FTTP users. By applying a detailed cost model to the outcome of the optimisation we are able to show that our LR-PON deployment strategy that minimises the overall protection capacity, rather than just minimising ?bre distances in the LR-PON, can signi?cantly reduce costs.
PUBLISHED
Keywords: Protected Long-Reach; network protection and resiliency; Optical networks; network optimization; Smart & Sustainable Planet